Living in the shadow of prison. Lessons from the Canadian experience in decarceration - Roberts, Julian V. (The British journal of criminology, 2004)
A number of jurisdictions, including England and Wales, have recently experienced rising prison populations and this has renewed the search for fresh alternatives to incarceration. Following the recommendations of the Home Office Sentencing Review of 2001, the Criminal Justice Bill 2002 contains a suspended term of imprisonment, which is a form of conditional sentence for England and Wales. Although conditional sentences of various kinds exist in many Western nations, the Canadian experience carries the most lessons for other jurisdictions. A conditional sentence of imprisonment designed to replace actual terms of custody was introduced in 1996. The offender is sentenced to a term of imprisonment, but discharges the sentence while living in the community, under supervision. As long as they comply with a number of conditions, offenders serving conditional sentences will not actually spend any time in a correctional institution. This paper evaluates the effectiveness of this sanction to date. Results indicate that the conditional sentence has occasioned a significant drop in the number of admissions to custody, and with only a minor degree of net widening. The paper concludes by drawing some general conclusions from the Canadian experience with this alternative to imprisonment